The Reality of Using Artificial Intelligence Technology in Teaching by Hail University Professors - Mahmoud, Khaled Mahgoub Abdullah (Journal of Ecohumanism, 2025)
The objective of the research was to ascertain the extent of Artificial intelligence technologies (AIT) employed by Hail University professors in their teaching, as well as the correlation between this usage and the following factors: scientific specialization, academic rank, years of university teaching experience, and gender (male/female). The researcher employed the descriptive approach and a questionnaire instrument to gather data. The research population comprised all professors at Hail University, totaling 1,175 from various colleges, encompassing both genders. The research sample was obtained through stratified random sampling, consisting of 296 individuals, representing 25% of the original population size. The data were statistically analyzed with the Statistical Package for Social Sciences (SPSS) software, yielding the following results: Professors at Hail University employ (AIT)in teaching to a moderate extent, with statistically significant variations in their usage linked to the type of specialization. The findings indicate that engineering faculty utilize (AIT) more extensively in their instruction, followed by health faculty, and then humanities faculty. The results indicated statistically significant differences among Hail University professors regarding their utilization of (AIT), influenced by academic rank, favoring assistant and associate professors, followed by lecturers, and lastly, full professors. No statistically significant variations exist among Hail University instructors regarding the utilization of Artificial intelligence (AI) tools in teaching, as related to the factors of teaching experience and gender (male/female). The findings indicated that teachers at Hail University predominantly employ administrative analytical (AIT)in their teaching, followed by devoted educational interactive (AIT), and subsequently strategies that facilitate the educational process. Based on these findings, the researcher offered several recommendations and suggestions for subsequent research.